2008
DOI: 10.1073/pnas.0705603105
|View full text |Cite
|
Sign up to set email alerts
|

Patched, the receptor of Hedgehog, is a lipoprotein receptor

Abstract: The Hedgehog (Hh) family of secreted signaling proteins has a broad variety of functions during metazoan development and implications in human disease. Despite Hh being modified by two lipophilic adducts, Hh migrates far from its site of synthesis and programs cellular outcomes depending on its local concentrations. Recently, lipoproteins were suggested to act as carriers to mediate Hh transport in Drosophila. Here, we examine the role of lipophorins (Lp), the Drosophila lipoproteins, in Hh signaling in the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 50 publications
3
64
1
Order By: Relevance
“…These data argue that colocalization of Dlp with Ptc in endocytic vesicles is not essential for Dlp function in Hh signaling. Consistent with this view, several studies have shown that endocytosis is not essential for Hh signaling in Drosophila wing discs (Callejo et al, 2008;Han et al, 2004b;Torroja et al, 2004). Our conclusion differs from a recent publication arguing that the GPI anchor of Dlp is required for its function in Hh signaling (Gallet et al, 2008).…”
Section: The Core Protein Is Essential For Dlp Function In Hh Signalingcontrasting
confidence: 56%
“…These data argue that colocalization of Dlp with Ptc in endocytic vesicles is not essential for Dlp function in Hh signaling. Consistent with this view, several studies have shown that endocytosis is not essential for Hh signaling in Drosophila wing discs (Callejo et al, 2008;Han et al, 2004b;Torroja et al, 2004). Our conclusion differs from a recent publication arguing that the GPI anchor of Dlp is required for its function in Hh signaling (Gallet et al, 2008).…”
Section: The Core Protein Is Essential For Dlp Function In Hh Signalingcontrasting
confidence: 56%
“…Hh associates with the Drosophila lipoprotein particle Lipophorin (Lpp) (Panáková et al, 2005) and these particles are necessary for normal Hh signaling (Callejo et al, 2008;Panáková et al, 2005). Here, we show that specific lipids contained within Lpp are required to decrease Smo levels and Smo-dependent Ci 155 stabilization in the absence of Hh.…”
Section: Introductionmentioning
confidence: 88%
“…Indeed, Lpp knockdown narrows the range of Hh target gene activation (Fig. 1Q,R) (Callejo et al, 2008;Panáková et al, 2005). Despite the reduced range of target gene activation in LppRNAi discs, Smo actually accumulates on the basolateral membrane as it would if Ptc activity were reduced.…”
Section: Lpp Is Required To Reduce Smo Accumulation On the Basolateramentioning
confidence: 99%
See 2 more Smart Citations